Active protein aggregates induced by terminally attached self-assembling peptide ELK16 in Escherichia coli - Wu, Wei (BioMed Central, 2011)
BACKGROUND: In recent years, it has been gradually realized that bacterial inclusion bodies (IBs) could be biologically active. In particular, several proteins including green fluorescent protein, β-galactosidase, β-lactamase, alkaline phosphatase, D-amino acid oxidase, polyphosphate kinase 3, maltodextrin phosphorylase, and sialic acid aldolase have been successfully produced as active IBs when fused to an appropriate partner such as the foot-and-mouth disease virus capsid protein VP1, or the human β-amyloid peptide Aβ42(F19D). As active IBs may have many attractive advantages in enzyme production and industrial applications, it is of considerable interest to explore them further. RESULTS: In this paper, we report that an ionic self-assembling peptide ELK16 (LELELKLK)(2 )was able to effectively induce the formation of cytoplasmic inclusion bodies in Escherichia coli (E. coli) when attached to the carboxyl termini of four model proteins including lipase A, amadoriase II, β-xylosidase, and green fluorescent protein. These aggregates had a general appearance similar to the usually reported cytoplasmic inclusion bodies (IBs) under transmission electron microscopy or fluorescence confocal microscopy. Except for lipase A-ELK16 fusion, the three other fusion protein aggregates retained comparable specific activities with the native counterparts. Conformational analyses by Fourier transform infrared spectroscopy revealed the existence of newly formed antiparallel beta-sheet structures in these ELK16 peptide-induced inclusion bodies, which is consistent with the reported assembly of the ELK16 peptide. CONCLUSIONS: This has been the first report where a terminally attached self-assembling β peptide ELK16 can promote the formation of active inclusion bodies or active protein aggregates in E. coli. It has the potential to render E. coli and other recombinant hosts more efficient as microbial cell factories for protein production. Our observation might also provide hints for protein aggregation-related diseases.